Docência universitária: concepções de prática pedagógica do professor da educação jurídica - Simões, Helena Cristina Guimarães Queiroz (2013)
The objective of this investigation was to know and discuss the conceptions of the Professors´ pedagogical practice who teach in law courses. Our focus is the superior teaching in Law Courses and their features according to their practice. As a result of the widening of Law Courses in Brazil in the last ten years and, because of the considerable rise of Professor´s staff, the literature on legal teaching is poor and outdated. In this sense, this study proposes to investigate which are the conceptions of pedagogical practice accomplished by professors, who are graduated in Law, and work in legal teaching and if they are ready to work according to a practice considerer contemporaneous. Four categories were pre-defined for the research: professional academic background; conceptions of teaching and learning; pedagogical knowledge and, interpersonal relations. This is an exploratory-analytical research with a qualitative and quantitative approach and it was used a mixed questionnaire as resource of investigation. The state of Amapá was chosen to be the research field, where 64 professors participated. The data for the closed questions were analyzed statiscally and for correlation (Spearman) the open questions, categorized based on the Content Analysis (Bardin, 2011). The results showed: lack of teaching formation for graduate classes; tendency; mostly, to less conservative behavior in the teaching and learning processes; highlighting of the experimental knowledge and, evidences of greater dialogue in the interpersonal relations. To sum up, the research searched for a triple conception of pedagogical practice in the teaching of Law: a) firstly, in a higher number, to keep a traditional conception, based on the focus of the content; oral method has been used as the only approach and the objective evaluation has been influenced as a consequence of external exams; b) the second, it is characterized by teachers who realize the necessity to overcome the traditional standard, however they do not know how, or they think they know, how to act into contemporaneous perspective; c) and the third conception, identified by a short group of professors who act into an emergent paradigm, shaped by the concern and search for teaching skills, methodological diversification, production of knowledge by the research and a wide development of the student. So, we have lived in a same academic environment, professors from different conceptions of pedagogical practice, who need to improve in order to reach a quality legal education.